PKLA SEBAGAI INOVASI MENEJERIAL PENDIDIKAN ISLAM DI MAN BONDOWOSO - Lukman Hakim; Ahmad Mudofi; Kutsiyah Kutsiyah (CV. ADIBA AISHA AMIRA, 2025)
This study aims to describe the implementation of the Religious Field Work Practice (PKLA) as a form of managerial innovation in Islamic education at MAN Bondowoso. The scope of this study includes the planning, implementation, and evaluation of PKLA activities systematically managed by the madrasah. This research employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation. The informants consisted of the principal, PKLA supervisors, and students. The results indicate that PKLA at MAN Bondowoso functions not only as a routine religious program but also as an innovative medium for strengthening students' religious character and social competence. From a managerial perspective, the program is designed through cross-sector coordination, structured scheduling, and collaboration with external religious institutions. The evaluation is carried out in stages to ensure the sustainability and effectiveness of the program. This study concludes that the implementation of PKLA at MAN Bondowoso represents a managerial innovation in Islamic education that significantly contributes to the development of students’ character and the enhancement of religious skills through practical experience.